A Study of Sediment Transport and Sedimentation Potential of the Proposed Timah Tasoh Western Diversion Canal - Siti Nur Aina Shamsulbahri (School of Environmental Engineering, Universiti Malaysia Perlis, 2015)
The objective of the report is made of to study sediment and erosion that proposed at Timah Tasoh Western Diversion Canal using HEC-RAS model. To stimulate short term and long term sediment transport (erosion and deposition) along the proposed Timah Tasoh Western Diversion Canal.